The incidence of goiter among students living in a group of mountain villages in the Black Sea region and their thyrotropin and thyroid hormone values - Teziç, Tahsin; Gedik, Yusuf; Baki, Ali; Üzüm, Kazım; Kumandaş, Sefer; Arslanoğlu, Mehmet; Demirci, Yaşar; Nuhoğlu, Asiye (The Turkish Journal of Pediatrics, 1985)
This study has been done in order to find the incidence of goiter among 732 school children, aged between 6 and 20 years who are living in a mountain village in the Province of Trabzon, and at the same time to determine the grades of goiter of the various age groups and also to determine the serum TSH, T4 and T3 values of the goitrous children. The results show that the incidence and the grades of goiter increase as the students get older. Although no clinical signs of hypothyroidism were found in these children, 16 percent of children with stage II goiter and 38 percent of children with stage III goiter were found to be chemically hypothyroidic.
Keywords: endemic goiter; hypothyroidism; school age